2013
DOI: 10.1097/meg.0b013e32835b7124
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of gallbladder disease in the very elderly

Abstract: More than 80% of the patients were operated on because of complicated gallstone disease. Although the outcomes of patients undergoing semielective cholecystectomy were similar to those of patients treated as outpatients, patients operated with acute cholecystitis presented extremely high morbidity and mortality rates. Thus, we can only recommend that early elective cholecystectomy be performed in elderly patients as soon as they are found to have symptomatic gallstones. Also, further trials are required to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
2
26
1
1
Order By: Relevance
“…14,18,19,25-29 While elective cholecystectomy can be performed safely in older patients, limited data in this population suggest higher rates of comorbid illness, higher conversion rates, longer lengths of stay, increased need for ICU care, and more complications in this population. 18,19,30-34 In a recent study of 81 octogenarians, Lupinacci et al reported a 34% mortality rate, 51% complication rate, and an 11-day mean length of stay when cholecystectomy was performed in the acute setting (N=30); 77% of these patients required ICU care and the mean ICU stay was 9.4 days. This is in contrast to elective/non-urgent cholecystectomy (N=51), where there was no mortality, a 12-14% complication rate, and a mean length of stay under three days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,18,19,25-29 While elective cholecystectomy can be performed safely in older patients, limited data in this population suggest higher rates of comorbid illness, higher conversion rates, longer lengths of stay, increased need for ICU care, and more complications in this population. 18,19,30-34 In a recent study of 81 octogenarians, Lupinacci et al reported a 34% mortality rate, 51% complication rate, and an 11-day mean length of stay when cholecystectomy was performed in the acute setting (N=30); 77% of these patients required ICU care and the mean ICU stay was 9.4 days. This is in contrast to elective/non-urgent cholecystectomy (N=51), where there was no mortality, a 12-14% complication rate, and a mean length of stay under three days.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Once complications occur and urgent hospitalization and/or cholecystectomy is necessary, the morbidity and mortality are significantly increased. 14,17-19 …”
Section: Introductionmentioning
confidence: 99%
“…However, several reports show that early cholecystectomy is safe even in the severe forms of the disease [22–24] or in the elderly population [2527]. In particular, a recent review of prospective and retrospective series (EL3) [28] did not show an increase in local postoperative complications in severe cholecystitis and confirmed that laparoscopic cholecystectomy is to be considered an acceptable indication for it, despite a demonstrated threefold conversion rate.…”
Section: Review Of Literaturementioning
confidence: 99%
“…9,10 Once these complications occur in the elderly, mortality and morbidity increase dramatically. 11-14 The reluctance to perform elective cholecystectomy in elderly patients is likely multifactorial and includes concerns about increased morbidity, mortality, and length of hospital stay due to the comorbidities and frailty commonly seen in this population. 15,16 In addition, it is difficult for physicians to predict the risk of developing gallstone-related complications and balance this risk with operative risk at the time of decision making.…”
Section: Introductionmentioning
confidence: 99%